ANALISIS PENGARUH KAPITALISASI PASAR DAN RASIO KEUANGAN TERHADAP RETURN SAHAM - AGUSTINUS SRI WAHYUDI; BENY BENY; DANIEL DANIEL (Media Bisnis, 2020)
Stock returns are very important and become the main reason or objective for investors in investing. This study studies the effect of market capitalization and financial ratios on corporate stock returns. The independent variables used in this study are market capitalization to symbolize a company's market value and financial ratios such as earnings per share, debt to equity, return on assets, and current ratio. While the dependent variable is stock returns. The objects used in this study are property and real estate companies listed on the Indonesia Stock Exchange during the 2012-2017 period. The samples used in this study were collected using non-probability methods with purposive sampling techniques. Researchers use multiple regression models to examine the effect of independent variables that affect stock returns. The results showed that market capitalization had a positive effect on stock returns. While earnings per share, debt to equity, return on assets, and current ratio have no effect on stock returns